2012
DOI: 10.1111/acv.12007
|View full text |Cite
|
Sign up to set email alerts
|

Nest site selection by the endangered black robin increases vulnerability to predation by an invasive bird

Abstract: Few studies have investigated the impacts of established invasive birds on the native threatened avifauna. However, measuring the levels of mortality in native birds from exotic birds can help with management decisions on whether or not such introduced species need to be controlled. The black robin Petroica traversi is an endangered bird endemic to the Chatham Islands of New Zealand. Black robins build cup-like nests either within tree cavities ('cavity' nests) or in the sub-canopy vegetation ('open' nests). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…3 The nest after predation Other studies also reported that predation was one of the most common causes of nest failure (Allen and Peters 2012;Massaro et al 2013;Fondell and Ball 2004). Nests located at sites with thicker litter may be better protected from predators because the thicker litter limits predator access to the nest and provides increased visual obstruction (Fondell and Ball 2004;Neto 2006).…”
Section: Resultsmentioning
confidence: 99%
“…3 The nest after predation Other studies also reported that predation was one of the most common causes of nest failure (Allen and Peters 2012;Massaro et al 2013;Fondell and Ball 2004). Nests located at sites with thicker litter may be better protected from predators because the thicker litter limits predator access to the nest and provides increased visual obstruction (Fondell and Ball 2004;Neto 2006).…”
Section: Resultsmentioning
confidence: 99%
“…. , [9,10), [10, ∞), and we denote the asymptotic frequency of the age-class starting at age x as f a x , 0 ≤ x ≤ 10. We can then compute f a x as…”
Section: How Old Are the Chatham Island Black Robins Petroica Traversi ?mentioning
confidence: 99%
“…This artificially increased reproductive success in combination with our assumption that the fertility and mortality rates are fixed over a long time period, results in an age pyramid whose shape may not be representative of the current population. Given that the current black robin population is restricted to only two small islands and includes fewer than 250 individuals, the species remains endangered [9]. Hence, knowing the age frequency of this population, and the associated fertility and mortality rates, is highly relevant to the future conservation management of this species; this is investigated in more detail in the parallel study 3 .…”
Section: How Old Are the Chatham Island Black Robins Petroica Traversi ?mentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation-related research, especially on island ecosystems that have been invaded by introduced species (Courchamp et al 2003), typically examines predation on native species by introduced species. In a New Zealand context, a well-supported idea is that native species (often birds, but also reptiles) have not coevolved with (typically) mammalian predators and are prone to falling prey to introduced predators because of a lack of evolved defences (Diamond & Veitch 1981;Towns et al 2001;Wilson 2004;Massaro et al 2012;Stanbury & Briskie 2015). Prior to human arrival c. 1280 AD, New Zealand did not have significant mammalian predators, so this niche was filled by avian predators -one of these being the kārearea.…”
Section: Introductionmentioning
confidence: 99%